2016
DOI: 10.1073/pnas.1609792113
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-309 targets the Homeobox gene SIX4 and controls ovarian development in the mosquito Aedes aegypti

Abstract: Obligatory blood-triggered reproductive strategy is an evolutionary adaptation of mosquitoes for rapid egg development. It contributes to the vectorial capacity of these insects. Therefore, understanding the molecular mechanisms underlying reproductive processes is of particular importance. Here, we report that microRNA-309 (miR-309) plays a critical role in mosquito reproduction. A spatiotemporal expression profile of miR-309 displayed its blood feeding-dependent onset and ovary-specific manifestation in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 47 publications
(59 reference statements)
4
93
1
Order By: Relevance
“…Previous studies have demonstrated the effectiveness of genome editing with the CRISPR/Cas9 system in other vector mosquitoes such as Anopheles stephensi (Gantz et al ., ), Anopheles gambiae (Hammond et al ., ), Ae. agypti (Basu et al ., ; Hall et al ., ; Zhang et al ., ; Li et al ., ) and Culex quinquefasciatus (Itokawa et al ., ). These studies demonstrated that the rate of mutagenesis remarkably varies across mosquito species, target DNA sites, and even sgRNAs targeting the same genomic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the effectiveness of genome editing with the CRISPR/Cas9 system in other vector mosquitoes such as Anopheles stephensi (Gantz et al ., ), Anopheles gambiae (Hammond et al ., ), Ae. agypti (Basu et al ., ; Hall et al ., ; Zhang et al ., ; Li et al ., ) and Culex quinquefasciatus (Itokawa et al ., ). These studies demonstrated that the rate of mutagenesis remarkably varies across mosquito species, target DNA sites, and even sgRNAs targeting the same genomic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated effective CRISPR/Cas9 genome editing in the mosquito Ae. aegypti (30)(31)(32)(33)(34), however these studies utilized a non-transgenic source of Cas9 limiting both survivorship and editing efficiencies. To overcome these previous limitations, and to reduce the complexity of injecting multiple components (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the significant limitations posed by previous genome editing tools, the clustered regularly interspaced short palindromic repeats/CRISPR-associated sequence 9 (CRISPR/Cas9) system, originally discovered in bacteria and archaea (14)(15)(16)(17)(18)(19)(20), has been adapted as a programmable (20,21) precision genome editing tool in a diversity of organisms (22)(23)(24)(25)(26)(27)(28)(29), including mosquitoes (30)(31)(32)(33)(34). Briefly, the CRISPR/Cas9 system is guided by a chimeric programmable synthetic short guide RNA (sgRNA) (20) that binds Cas9 directing it to a user specified genomic DNA target sequence, via Watson-Crick base pairing between the sgRNA and the target DNA sequence, thereby generating site-specific double-strand (ds) dsDNA breaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26,27 However, it is not easy to use these methods in other lepidopterans. A recently developed genome-editing method, the clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) system, [28][29][30] has been successfully used as a new method for investigating gene function in various Diptera, [31][32][33][34][35] Amphipoda, 36 Diplostraca, 37 Decapoda, 38 Coleoptera, 39 Lepidoptera 27,[40][41][42][43][44][45][46] and Orthoptera. 47,48 Successful applications of CRISPR/Cas9 in insect pest species could provide a promising alternative strategy for genetic manipulation of agricultural insect pests.…”
Section: Introductionmentioning
confidence: 99%